Freelancing for journalists - Canter, Lily; Wilkinson, Emma (Loondon ; New York : Routledge, 2020)
Freelancing for Journalists offers an authoritative, practical and engaging guide for current and aspiring journalism freelances, exploring key aspects of the role including pitching a story, networking, branding and navigating freelance laws and rights. Featuring case studies from experienced freelance journalists working in the UK, US, Asia and Australia, the book addresses the evolving media landscape and provides valuable tips on how to become established as a successful journalist across a variety of platforms. The authors also explore practical aspects of the trade including tips for setting up a business, managing tax and legal issues, getting paid and earning additional income in related sectors. This book is an invaluable resource for both students and professionals who are interested in taking the next step into freelance journalism work.
OCLC-licensed vendor bibliographic record.
Keywords: Freelance journalism -- Vocational guidance; SOCIAL SCIENCE / Media Studies